1990
DOI: 10.1128/jb.172.12.6818-6825.1990
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetic organization of incompatibility group P degradative plasmids

Abstract: Plasmids that encode genes for the degradation of recalcitrant compounds are often examined only for characteristics of the degradative pathways and ignore regions that are necessary for plasmid replication, incompatibility, and conjugation. If these characteristics were known, then the mobility of the catabolic genes between species could be predicted and different catabolic pathways might be combined to alter substrate range. Two catabolic plasmids, pSS50 and pSS60, isolated from chlorobiphenyl-degrading str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 35 publications
2
44
1
Order By: Relevance
“…2). Members of the IncP plasmid group have been shown to be highly conserved despite the fact that they have been isolated from diverse genera of bacteria in different parts of the world (11,54,60). Antibiotic resistance, mercury resistance, and other catabolic genes have previously been identified on diverse IncP plasmids (11,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Members of the IncP plasmid group have been shown to be highly conserved despite the fact that they have been isolated from diverse genera of bacteria in different parts of the world (11,54,60). Antibiotic resistance, mercury resistance, and other catabolic genes have previously been identified on diverse IncP plasmids (11,54).…”
Section: Discussionmentioning
confidence: 99%
“…The latter group of plasmids consist predominantly of those known to contain antibiotic resistance genes or encode virulence determinants associated with infectious diseases (5,29,52). In contrast, catabolic plasmids, which have been identified in many nonpathogenic soil bacteria (49), have been shown to transfer among bacteria, thus disseminating genes encoding the metabolism of environmentally relevant compounds (11). For example, plasmids encoding the catabolism of toluene, camphor, naphthalene, and 2,4-dichlorophenoxyacetate are known (3,12,45,64).…”
mentioning
confidence: 99%
“…The toxicity assay was performed using a bioluminescent bioreporter Acinetobacter strain DF4/ PUTK2 that had been genetically modified by conjugation (Abd-El-Haleem et al, 2006) to contain the PUTK2 plasmid (Burlage et al, 1990), with the Tn4431 lux transposon downstream of a putative plasmid maintenance promoter to produce continual visible bioluminescence light. Bioluminescence was measured at 5 min regular time intervals from zero to 480 min by a luminometer (LumiStar, Galaxy, BMG, Germany).…”
Section: Residual Of Cu (Ii) Toxicity Assaymentioning
confidence: 99%
“…Initial digests of pSS60 with Sph I indicated that it was 10 kb larger than pSS50 (3,22). The restriction map of pSS60 is very similar to pSS50 excepting that it has a unique 7kb region which does not hybridize to pSS50 ( Figure 6).…”
Section: Direct Extraction Of Nucleic Acids From Sedimentsmentioning
confidence: 99%